2022
DOI: 10.3389/fpsyt.2022.832352
|View full text |Cite
|
Sign up to set email alerts
|

Second Wave of COVID-19 Pandemic in Argentinian Population: Vaccination Is Associated With a Decrease in Depressive Symptoms

Abstract: BackgroundSince the irruption of the coronavirus disease 2019 (COVID-19) the planet has submerged in a time of concern and uncertainty, with a direct impact on people's mental health. Moreover, the recurrent outbreaks that periodically harry different regions of the world constantly refocus people's concerns to the pandemic. Yet, each new wave heats the diverse countries in different situations, including the advances in their vaccination campaigns. In this research, we studied the levels of the general anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…However, the symptoms of GAD and depression in our country correlated inversely with the accumulation of vaccine doses applied. These data are in agreement with our previous observations, showing that vaccination is associated with a decrease in depressive symptoms during the second wave of the COVID-19 pandemic in the Argentine population [ 13 ]. Also, compared with unvaccinated populations, vaccinated populations had a significantly lower prevalence rate of depression and anxiety in a cross-sectional study performed in Bangladesh during the second semester of 2021 [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, the symptoms of GAD and depression in our country correlated inversely with the accumulation of vaccine doses applied. These data are in agreement with our previous observations, showing that vaccination is associated with a decrease in depressive symptoms during the second wave of the COVID-19 pandemic in the Argentine population [ 13 ]. Also, compared with unvaccinated populations, vaccinated populations had a significantly lower prevalence rate of depression and anxiety in a cross-sectional study performed in Bangladesh during the second semester of 2021 [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…We have reported that in May 2021, the prevalence of GAD and depression reached values ​​of 57.25% and 54.39%, respectively, considering a population restricted to the metropolitan area of ​​Buenos Aires [ 13 ]. Here, ​​we found similar values to those ones, even considering a population spread throughout the entire country.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, although we observed a slight decrease in general anxiety, the effect of vaccination on general depression and anxiety outcomes, measured with PHQ-2 and GAD-2, respectively, was not significant. However, previous studies conducted in adults from the United States, 24 Turkey, 57 Argentina, 58 and China, 59 and health professionals from Turkey 27 reported that those with at least one dose of the vaccine against COVID-19 have lower scores on the depression scales, measured with the PHQ-4, PHQ-9, and the Beck Depression Inventory, and on anxiety scales, measured with the GAD-7 and the Beck Anxiety Inventory. The mechanisms and causes of depression and anxiety in older adults are related to psychosocial factors of loneliness and loss, and neuroendocrine and vascular disorders.…”
Section: Summary Of Resultsmentioning
confidence: 87%